HDAC6 Regulates the Fusion of Autophagosome and Lysosome to Involve in Odontoblast Differentiation - Zhan, Yunyan; Wang, Haisheng; Zhang, Lu; Pei, Fei; Chen, Zhi (Frontiers in Cell and Developmental Biology, 2020)
Odontoblast differentiation is an important process during tooth development. During the process pre-odontoblasts go through elongation, polarization, and finally become mature secretory odontoblasts. Many factors had been proved to regulate the process, our previous studies showed that autophagy played an important role in tooth development and promoted odontoblastic differentiation in an inflammatory environment. However, what modulates autophagy during odontoblast differentiation process remains unknown. In this study, we found HDAC6 involved in odontoblast differentiation process. The capacity of odontoblastic differentiation of human dental papilla cells was impaired when HDAC6 was inhibited. Moreover, we found HDAC6 and autophagy showed a similar expression pattern during odontoblast differentiation process both in vivo and in vitro, the HDAC6 and autophagy related proteins ATG5, LC3 expression increased with differentiation process. When HDAC6 was knocked down, LC3 puncta increased in cytoplasm, autophagy substrate P62 also increased, that suggested the autophagy flux was affected in human dental papilla cells. Then we detected the mechanism during odontoblastic differentiation and found HDAC6 substrate acetylated-Tubulin up-regulated when HDAC6 was knocked down, LAMP2, LC3 and P62 proteins increased, while ATG5 and Beclin1 showed no obvious change. Autophagosomes and lysosomes increased and showed diffused distribution in cytoplasm with mRFP-GFP LC3 plasmid labeling. It suggested the fusion between autophagosome and lysosome was blocked, thus affecting the autophagy process during odontoblast differentiation. In conclusion, HDAC6 regulated the fusion of autophagosome and lysosome to involve in odontoblast differentiation. It provides a new viewpoint into the role of autophagy in odontoblast differentiation.